Jurisprudential Origins of Digital Drugs - Music - and their Legal Adaptation: A Comparative Study With Jordanian Law - Al-hajahjeh, Jaber; Rababah, Basema (Jordan Journal of Islamic Studies, 2024)
This study aims to clarify the jurisprudential origins of digital drugs, specifically music, and compare their legal status in Jordanian Law. Digital drugs, referring to different sound files exploited to trick the brain using sound waves in a way that induces addiction, are an old phenomenon that has recently gained recognition and spread. To achieve the study purpose, the research relied heavily on an inductive method, then a deductive one, to understand how musical drugs affect the brain and highlight similarities between traditional drugs and it. Accordingly, a suitable Islamic judgment was deduced. The study resulted in several key conclusions: digital drugs or sound files used to trick the brain invoking relaxation, pleasure, and loss of consciousness, much like intoxicating substances and drugs. It was determined that the ruling of these musical drugs is forbidden in Sharia, as they act as regular traditional drugs.